Determination and comparison of biochemical characteristics in an ex-situ collection of sweet cherry cultivars in Morocco - Zahra El kettabi; Kaoutar Elfazazi; Abdelmajid Haddioui; Abdelaaziz Alaoui; Atman Adiba; Kamal El fallah; Chaimae El-rhouttais; Jamal Charafi (Discover Food)
Abstract In Morocco, limited studies have systematically evaluated the biochemical composition of sweet cherry germplasm under uniform environmental conditions. This study aimed to determine and compare key biochemical traits in an ex-situ collection of 19 sweet cherry cultivars grown under identical agronomic management over two consecutive years (2021–2022). A comprehensive biochemical profiling was conducted, included total polyphenol content (TPC), total flavonoid content (TFC), total anthocyanin content (TAC), soluble sugars content (SSC), and antioxidant capacity. The results revealed significant genotypic variation (p < 0.01) for all biochemical traits, with substantial interannual fluctuations attributable to environmental factors. Across both years, TPC ranged from 585.41 to 788.55 mg GAE/100 g DW, TFC from 12.43 to 311.32 mg EC/100 g DW, and TAC from 1.06 to 235.68 mg ECya-3-Glu/100 g DW. SSC exhibited pronounced variation, ranging from 2.39 to 58.96 mg EG/100 g DW. Antioxidant capacity varied significantly, with DPPH scavenging activity ranging from 20.03 to 29.53 mM Teq/g DW and ABTS from 32.13 to 55.18 mM Teq/g DW. Notably, climatic data indicated that 2022 experienced elevated temperatures and higher solar radiation relative to 2021, influencing the biosynthesis of bioactive compounds. These results provide a comprehensive characterization of the biochemical diversity among sweet cherry cultivars under Moroccan environmental conditions. The generated database constitutes a valuable resource for breeding programs in Morocco and will support farmers and the agri-food industry in making informed varietal choices to optimize fruit quality and market potential.